Chronic sleep deprivation disturbs energy balance modulated by suprachiasmatic nucleus efferents in mice - Tingting Du; Shuailing Liu; Honghong Yu; Tian Hu; Lina Huang; Lanyue Gao; Lihong Jia; Jiajin Hu; Yang Yu; Qi Sun (BMC Biology)
Abstract Background Epidemiologic researches show that short sleep duration may affect feeding behaviors resulting in higher energy intake and increased risk of obesity, but the further mechanisms that can interpret the causality remain unclear. The circadian rhythm is fine-tuned by the suprachiasmatic nucleus (SCN) as the master clock, which is essential for driving rhythms in food intake and energy metabolism through neuronal projections to the arcuate nucleus (ARC) and paraventricular nucleus (PVN). Results We showed that chronic SD-induced aberrant expressions of AgRP/NPY and POMC attributed to compromised JAK/STAT3 signals and reduced energy expenditure in the mice, which can be rescued with AAV-genetic overexpression of BMAL1 into SCN. The potential mechanism may be related to the disruptions of SCN efferent mediated by BMAL1. Conclusions Chronic SD impairs energy balance through directly dampening BMAL1 expression, probably in the transcription level, in the SCN, which in turn affects the neuron projections to ARC and PVN. Remarkably, we provide evidence that may explain the causal mechanisms associated with sleep curtailment and obesity in adolescents. Graphical Abstract